2017
DOI: 10.1002/sctm.17-0035
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Fresh, Allogeneic Mesenchymal Stem Cells for Severe Refractory Feline Chronic Gingivostomatitis

Abstract: Mesenchymal stem cells (MSCs) have potent immunomodulatory functions and are a promising therapy for immune‐mediated inflammatory disorders. We previously demonstrated the efficacy of fresh, autologous, adipose‐derived MSCs (ASCs) to treat feline chronic gingivostomatitis (FCGS), a chronic oral mucosal inflammatory disease similar to human oral lichen planus. Here, we investigate the use of fresh allogeneic ASCs for treatment of FCGS in seven cats. Radiolabeled ASCs were also tracked systemically. Each cat rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
116
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(124 citation statements)
references
References 65 publications
7
116
0
1
Order By: Relevance
“…Additional studies in which MSC are culture‐expanded, characterized, and administered at various doses are needed to more definitively associate study results with MSC alone as well as with MSC dose. Radiolabeling of MSC and tracking their migration with nuclear scintigraphy as recently has been done in cats and horses also could be considered to assess MSC engraftment in the kidney and association with clinical outcome, but renal clearance of the radiolabel may complicate the interpretation of results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies in which MSC are culture‐expanded, characterized, and administered at various doses are needed to more definitively associate study results with MSC alone as well as with MSC dose. Radiolabeling of MSC and tracking their migration with nuclear scintigraphy as recently has been done in cats and horses also could be considered to assess MSC engraftment in the kidney and association with clinical outcome, but renal clearance of the radiolabel may complicate the interpretation of results …”
Section: Discussionmentioning
confidence: 99%
“…Some of the specific challenges described above are avoided with 34,35 The source of adipose tissue used for SVF in our study varied among patients. Multiple studies in dogs and people have shown differences in MSC yield as well as replication rate and differentiation ability of MSC depending on the source of adipose tissue (eg, omental versus SC).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that feline MSC has therapeutic effects of gingivostomatitis, asthma, chronic kidney disease, and enteritis in feline medicine. (16)(17)(18)(19). Feline MSC has been isolated from bone marrow, adipose tissue and amniotic membrane (11,20,21).…”
mentioning
confidence: 99%
“…These are species-specific Ab targeting NGF which has an important role in pro-nociception. In addition, recent research has indicated a potential efficacy of the use of autologous mesenchymal stem cell therapy for the treatment of severe refractory gingivostomatitis, an important cause of chronic pain in cats (8 Introduction/Objective: In several EU and some US states, medical marijuana is an option for people suffering from various ailments and seeking relief. As cannabis is now sold as an oil extract, it has become a conceivable option for dogs too.…”
mentioning
confidence: 99%
“…These are species-specific Ab targeting NGF which has an important role in pro-nociception. In addition, recent research has indicated a potential efficacy of the use of autologous mesenchymal stem cell therapy for the treatment of severe refractory gingivostomatitis, an important cause of chronic pain in cats (8). stress and anxiety, arthritis and cancer pain, but no information on its pharmacokinetics is available in dogs.…”
mentioning
confidence: 99%